Multilayer Thin Films : Sequential Assembly of Nanocomposite Materials. - Decher, Gero (Wiley, 2012)
This second, comprehensive edition of the pioneering book in this fi eld has been completely revised and extended, now stretching to two volumes. The result is a comprehensive summary of layer-by-layer assembled, truly hybrid nanomaterials and thin fi lms, covering organic, inorganic, colloidal, macromolecular, and biological components, as well as the assembly of nanoscale fi lms derived from them on surfaces. These two volumes are essential for anyone working in the field, as well as scientists and researchers active in materials development, who needs the key knowledge provided herein for linking the field of molecular self-assembly with the bio- and materials sciences.